From prevention of pin-tract infection to treatment of osteomyelitis during paediatric external fixation. (December 2016) - Ceroni, Dimitri; Grumetz, Catherine; Desvachez, Odile; Pusateri, Sophie; Dunand, Pierre; Samara, Eleftheria
Pin-tract infection (PTI) is the most commonly expected problem, or even an almost inevitable complication, when using external fixation. Left unteated, PTI will progress unavoidably, lead to mechanical pin loosening, and ultimately cause instability of the external fixator pin–bone construct. Thus, PTI remains a clinical challenge, specifically in cases of limb lengthening or deformity correction. Standardised pin site protocols which encompass an understanding of external fixator biomechanics and meticulous surgical technique during pin and wire insertion, postoperative pin site care and pin removal could limit the incidence of major infections and treatment failures. Here we discuss concepts regarding the epidemiology, physiopathology and microbiology of PTI in paediatric populations, as well as the clinical presentations, diagnosis, classification and treatment of these infections.